Prevalence and factors associated with frailty among incident kidney transplant patients: a cross-sectional study - Raoni de Oliveira Domingues-da-Silva; Helady Sanders-Pinheiro; Emiliana Holanda Pedrosa; Camila Mendes dos Santos; Jerônimo Junqueira Junior; Ronaldo de Matos Esmeraldo; Paula Frassinetti Castelo Branco Camurça Fernandes; Claudia Maria Costa de Oliveira; Tainá Veras de Sandes-Freitas (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Evidence on frailty prevalence in Brazilian patients with kidney transplant (KT) is scarce. OBJECTIVES: To estimate frailty prevalence in pre-KT patients and its association with functional, cognitive, and laboratory anomalies. DESIGN AND SETTING: Cross-sectional descriptive study included adult KT candidates assessed within 24 hours before KT, at two medical centers in Northeast Brazil. METHODS: Frailty was classified as non-frail (scores 0–1), intermediate frail (score 2), or frail (scores 3–5), using Fried et al. criteria. Patients were divided into: Non-frail (0–1) and Frail (≥ 2) groups. Katz and Lawton’s scales assessed the dependence on basic (ADLs) and instrumental (IADLs) activities of daily living, respectively. Montreal Cognitive Assessment was used to evaluate cognition. Laboratory tests were performed during pre-KT evaluation. RESULTS: Among 82 patients, most were male (80.5%), mixed-race (76.8%), and 48.8 ± 14.9-years-old. The Frail group (63.4%) comprised 34.1% intermediate frail, and 29.3% frail individuals. This group had a higher prevalence of hypertension (90.4% vs. 70%, P = 0.018), rheumatological diseases (15.4% vs. 0%, P = 0.024), cognitive impairment (71.0% vs. 40.7%, P = 0.020), dependence on ADLs (32% vs. 0%, P < 0.001) and IADLs (82% vs. 56.7%, P = 0.014), lower hemoglobin (11.9 ± 2.7 g/dL vs. 13.4 ± 1.8 g/d, P = 0.005), and lower creatinine levels (7.1 mg/dL, IQR 6–10 vs. 9.1 mg/dL, IQR 7–11, P = 0.044). CONCLUSIONS: Pretransplant frailty was prevalent and associated with functional disability, cognitive impairment, and biomarkers indicating sarcopenia. Early frailty assessment and identification of modifiable factors are essential.